Smart Power ICs technologies and applications - Murari, B.; Bertotti, F.; Vignola, G.A; Andreini, A. (Springer, 1996)
In recent years power integrated circuit technology has grown to become a major business worth more than a billion dollars. This book provides a survey of the state-of-the art of the technology and future trends in the new family of SmartPower ICs and describes design, applications in a variety of fields ranging from automotive to telecommunications, reliability evaluation and qualification procedures.